Preparing undergraduate students for career success through case study writing and implementation in real job contexts - Francisco Gerardo Barroso Tanoira (Nova Scientia, 2017)
The objective of this study was to test the effectiveness of a procedure to train undergraduate students to write and implement case studies for improving their learning ex periences, adapt to the labor environment and be better prepared for career success. Method . Undergraduate students in social service internships at the Higher State Auditing Office in the states of Yucatan, Campeche and Q. Roo, in the Southeast of Mexico, under the guidance of Government Auditors, designed case studies to be implemented with their classmates following the procedure studied in this document, prepared by the author of this research. Results . R esults showed that after t his experience, implementer students were more motivated for learning, more interested in case studies, more confident at working with others and were satisfied with learning. This was compared to the learning through traditional methods, according to thei r perception. Conclusion . T his case study procedure is effective for preparing students for improving their technical and socio - emotional competencies in their preparation for career success, but also a professional development oppo rtunity for the Auditors. Learning to write and implement cases help learning and adaptation to work environment. It is learning how to learn and be prepared for career success through experiences such as this in real job contexts.